Analysis and design different solutions of steel truss based on Continente Bom Dia project - Kardel, Wojciech (2020)
This project presents various design solutions for the roof structure of a Continente Bom Dia supermarket. In this project, was calculated the utilization of already built truss, checking the limit states according to Eurocode 3. In the next part of the project four different solutions were designed, with the same height and span. Calculated percentage of use of newly designed solutions (using Eurocode 3), results were compared with the truss built in the baseline construction of the Continente Bom Dia supermarket. In designing trusses it was important to maximize the percentage of using each cross-section and minimize the weight of the steel. In the embodiment of structural steel, an important and costly element is also the fire retardant paint coating. The studied solutions have been compared due to the cost of steel and fire retardant paint.